1996
DOI: 10.1080/00288233.1996.9513213
|View full text |Cite
|
Sign up to set email alerts
|

The place of C4grasses in temperate pastures in Australia

Abstract: This paper explores the potential role of summer-active C 4 grasses in temperate areas in Australia from an ecological perspective. The main functional differences between C3 and C4 plants are briefly outlined. Taken together, the characteristics and environmental requirements of introduced C3 perennial pasture cultivars lessen their natural competitive ability except in well-watered and cool habitats. C4 plants are more competitive under conditions of high temperature and solar radiation. Within the C4 group,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 103 publications
1
29
0
Order By: Relevance
“…The distinction between temperate and subtropical biology is clearly a primary functional basis for the separation of clusters, confirming the findings of previous research by indicating that the distinction between C3 and C4 photosynthesis types can be broadly used to predict the responses of plants to climate (Hattersley & Watson 1992;Johnston 1996). The cluster analysis confirmed that a large proportion of the variance in species climate envelopes can be accounted for by a division into two groupings: (i) the C3 species, and (ii) the C4 species plus R. racemosum.…”
Section: The Cluster Analysis and Plant Functional Typessupporting
confidence: 74%
“…The distinction between temperate and subtropical biology is clearly a primary functional basis for the separation of clusters, confirming the findings of previous research by indicating that the distinction between C3 and C4 photosynthesis types can be broadly used to predict the responses of plants to climate (Hattersley & Watson 1992;Johnston 1996). The cluster analysis confirmed that a large proportion of the variance in species climate envelopes can be accounted for by a division into two groupings: (i) the C3 species, and (ii) the C4 species plus R. racemosum.…”
Section: The Cluster Analysis and Plant Functional Typessupporting
confidence: 74%
“…The potential for summer-active C 4 grasses to contribute to pasture production in temperate areas of Australia has been explored (Johnston & Sutherland 1996) from the ecological perspective. Given the relatively wide adaptive range of C 4 grasses, the authors concluded that they would provide versatility in responses to changed conditions such as grazing.…”
Section: Potential Of Tropical Pasturesmentioning
confidence: 99%
“…Extra benefits included reduced rates of both soil pH decline and deep drainage of excess water to water tables. Both occur when C 3 grasses are unable to grow in summer conditions, and they represent a major threat to the sustainability of agriculture in some areas of Australia (Johnston & Sutherland 1996).…”
Section: Potential Of Tropical Pasturesmentioning
confidence: 99%
“…In temperate and subtropical areas, tropical (C4) grasses have the potential to increase forage production during summer, when growing conditions are not ideal for C3 temperate grasses (Davies and McNaughton 1980;Johnston 1996;Crush and Rowarth 2007). As well as having better growth potential, some tropical grasses have shown good adaptation to saline soils (Loch et al 2004), drought conditions (Pitman 2001), soils with low or high pH (Robinson et al 1993), infertile soils (Loch 1980), seasonal flooding (Baruch 1994;Imaz et al 2015a) and other environmental stresses, whereas temperate grasses showed poor persistence (Crush and Rowarth 2007).…”
Section: Introductionmentioning
confidence: 99%